Macrocyclic bis-urea receptor: Synthesis, crystal structure and phosphate binding properties. Issue 10 (7th March 2019) - Shu, Xi; Wang, Ruyu; Fan, Yu; Li, Shoujian; Huang, Chao
Graphical abstract: Highlights: A macrocyclic bis-urea and two acyclic bis-urea analogues have been synthesized. NMR titrations indicates thatL1 has high selectivity to H2 PO4 − . L1 exhibits higher binding affinity with H2 PO4 − thanL2 andL3 . XRD analysis shows thatL1 have different conformations in solid structure. Abstract: A macrocyclic bis-urea receptor (L1 ) and two acyclic bis-urea analogues (L2 andL3 ) have been synthesized. The crystal structure ofL1 was obtained. The experimental results show that the receptorL1 has high selectivity to H2 PO4 − . Meanwhile, compared with the acyclic receptorsL2 andL3, L1 has higher binding ability to H2 PO4 − . The results of density functional theory (DFT) calculations deepened our understanding onL1 conformations stability and its anion-binding property.